KINERJA UPTD PELAYANAN SOSIAL KAMPUNG INVESTASI HATI DALAM PENANGANAN LANJUT USIA TERLANTAR DAN PENYANDANG DISABILITAS MENTAL DI KABUPATEN TABANAN - Pramita Dewi, Ni Wayan; Supriliyani, Ni Wayan; Dwi Wismayanti, Kadek Wiwin (CITIZEN CHARTER, 2021)
The UPTD Kampung Investasi Hati as a Social Welfare Institution in dealing high number of neglected elderly and people with mental disabilities in Tabanan Regency carries a program, namely Kampung Investasi Hati (Kata Hati). The purpose of this study was to determine performance of UPTD Kampung Investasi Hati in handling neglected elderly and people with mental disabilities in Tabanan Regency. The research method used is descriptive qualitative. The indicators used to analyze performance of the UPTD Kampung Investasi Hati uses the performance measurement theory by Dwiyanto, namely Productivity, Service Quality, Responsiveness, Responsibility and Accountability. The results showed that the performance of the UPTD Kampung Investasi Hati was not running optimally. There are obstacles that cause service delivery not optimal, ranging from less than optimal socialization, limited number of employees and the lack of budget in financing programs and activities. Keywords: Performance, Social Service, Neglected Elderly and People with Mental Disabilities